2000
DOI: 10.1016/s0304-3959(99)00258-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pain expression between male and female newborn infants

Abstract: The study of neonatal gender differences in pain expression is important since neonatal pain behavior occurs prior to any learned reaction pattern. The objective of this study was to verify the presence of gender differences in pain expression in preterm and term newborn infants. Sixty-five consecutive neonates (37 female and 28 male infants) with gestational age between 28 and 42 weeks and with 25-120 h of life were studied. Healthy term neonates required a capillary puncture for PKU screening and clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 24 publications
4
27
0
8
Order By: Relevance
“…Divergences could be linked to factors related to the characteristics of the neonates themselves or of the healthcare professionals working there. 7,10,[13][14][15][16][17] Fentanyl (93%) was the most prescribed analgesic in this study, in a similar manner to what has been reported by Anand and Selanikio 18 and Castro et al. 8 In contrast, Stevens et al 19 found that morphine was given twice as often as fentanyl at Canadian neonatal units.…”
Section: Discussionsupporting
confidence: 79%
“…Divergences could be linked to factors related to the characteristics of the neonates themselves or of the healthcare professionals working there. 7,10,[13][14][15][16][17] Fentanyl (93%) was the most prescribed analgesic in this study, in a similar manner to what has been reported by Anand and Selanikio 18 and Castro et al. 8 In contrast, Stevens et al 19 found that morphine was given twice as often as fentanyl at Canadian neonatal units.…”
Section: Discussionsupporting
confidence: 79%
“…A few studies suggest that sex differences in pain/analgesia develop by the early neonatal period in the rodent [37,110,192], although it is not clear whether sex differences are observed that early in humans [65,80,152]. In contrast, beginning around puberty, age-dependent sex differences occur for several types of pain in humans.…”
Section: How Does Pain Chronicity Contribute To Sex Differences In Pamentioning
confidence: 99%
“…Recent experimental studies have addressed these sex differences in behavioral expression after early postnatal noxious stimulation Murphy, 2007, 2010;Negrigo et al, 2011) and sex-specific behavioral alterations between preterm and agematched infants (Guinsburg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%